The Urgence of Gender Responsive Marriage Guidelines as an Effort for Happy and Prosperous Family - Susanti, Sri; Munawaroh, Siti; Marsiwi, Dwiati (MUADDIB Jurnal Kependidikan dan Keislaman, 2024)
Marriage guidance is a stage that must be passed by prospective brides and grooms in an effort to form a happy and prosperous family. This study aims to describe the urgency of marriage guidance and analyze the influence of guidance programs on divorce rates, as well as to determine the obstacles faced by the Office of Religious Affairs in implementing marriage guidance for prospective brides and grooms in Ponorogo district. This study uses a descriptive method with a qualitative approach. The data collection instruments used are observation, interviews, and documentation. Analysis of research data uses data reduction, data presentation, and drawing conclusions. Marriage guidance is a stage that must be passed by prospective brides and grooms before carrying out the marriage contract in order to prepare themselves in building a household so that a happy and prosperous family is realized. The Ponorogo Regency Religious Affairs Office has implemented marriage guidance for prospective brides and grooms quite effectively in reducing the divorce rate, with 1,513 cases of divorce lawsuits and 556 cases of divorce lawsuits occurring in 2019, decreasing to 1,412 cases of divorce lawsuits and 498 cases of divorce lawsuits in 2020, and slightly increasing to 1,450 cases of divorce lawsuits and 540 cases of divorce lawsuits in 2021.